Retinal venous pressure in chronic smokers - Vahedian, Zakieh (EPMA J, 2015)
BACKGROUND: The overall aim of this study was to determine retinal venous pressure (RVP) in healthy chronic smokers and compare values to those of healthy non-smokers. METHODS: Both eyes of 25 healthy chronic smokers and 41 healthy non-smokers were included. Measurements of RVP were performed by means of contact lens ophthalmodynamometry. Ophthalmodynamometry is done by applying increasing force on the eye via a contact lens. If a spontaneous venous pulsation was present, it was noted. If not, the compressive force was increased until the first venous pulsation was detected, and the measurement value was fixed and read. RVP was calculated as the sum of pressure increase induced by the instrument and intraocular pressure. RESULTS: Smokers had a significantly higher frequency of spontaneous venous pulsations than non-smokers (p < 0.001). Mean values of RVP were slightly lower in smokers than in non-smokers: 15.3 and 15.5 (smokers) versus 15.9 and 16.2 (non-smokers) for the right and left eye, respectively; however, the difference in RVP between the two groups did not reach significance. There was no significant difference in blood pressure between the two groups, but heart rate was significantly higher in smokers (p = 0.043). CONCLUSIONS: RVP values may differ in healthy smokers than in non-smokers. Therefore, smoking habits should be considered when interpreting RVP results.